Product Cycle Model and the Location Structure of Finnish Industries - Kimmo Niiranen (European Regional Science Association (ERSA), 2001)
Different variations of the product cycle model (cf. e.g., Malecki 1991) have been used in the analysis of regional change. The basic idea of the model is simple: products go through four stages from innovation to growth, maturity and decline. The locational factors are different in the different stages of the product cycle, and this has impacts on regional development. During the innovation period certain functions are centred in metropolitan regions and during the mature stage of the cycle in peripheral regions. This conditions the regional division of labour in the case of an individual country as well as in the global economy. This paper makes an attempt to find out whether the changes in the location of manufacturing industries have been in accordance with the assumptions of the product cycle model in Finland from the 1970s to the 1990s. The empirical observations are made on the basis of a large data set covering employment figures on 80 manufacturing industries the regional division being Helsinki metropolitan region vs. rest of Finland. Observations Aconcerning Sweden are used as a standard of comparison. The empirical findings of this paper can be summarised as follows: the location structure of the Finnish manufacturing industries has evolved from the 1970s to the 1990s so that the Helsinki metropolitan region can be considered as a forerunner of development or conductor of growth. It can be argued that the role of Helsinki for Finland has been similar to the role of Stockholm for Sweden. At he end of the paper some remarks are made concerning whether the observations can be interpreted from the point of view of regional policy, and to what extent changes follow the pattern outlined above in the present global economy.
Keywords: 330